Modeling of Compressor Performance Deterioration Due to Erosion - A. Hamed; W. Tabakoff; D. Singh (International Journal of Rotating Machinery)
This paper presents the results of a simulation of compressor performance deterioration due to blade erosion. The simulation at both design and off-design conditions is based on a mean line row by row model, which incorporates the effects of blade roughness and tip clearance. The results indicate a pronounced effect of blade erosion on the compressor adiabatic efficiency and a lesser effect on the pressure ratio. The loss in performance is mainly caused by the increased blade surface roughness and was highest at 100% speed.